Correction to: Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes (Acta Neuropathologica, (2023), 10.1007/s00401-023-02561-5) - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
In the original publication, incorrect version of Fig. 3 and wrong format of Table 1 were published. Specifically, the labels in Fig. 3 were missing and columns of Table 1 were not in the right format. The correct versions of Fig. 3 and Table 1 are shown below. The original article has been corrected.
CRIS-Team Scopus Importer:2023-05-05